Optimisation of screen printing process for functional printing. Issue 5 (2nd September 2019) - Ali, Muhammad; Lin, Long; Faisal, Saira; Sahito, Iftikhar Ali; Ali, Syed Imran
Abstract : Purpose: The purpose of this study is to explain the effects of screen printing parameters on the quantity of ink deposited and the print quality in the context of printing of functional inks. Both these aspects of printing are crucial in the case of conventional and functional printing. This is because, in the case of conventional printing, the quantity of ink deposit affects the color strength while in the case of functional printing, it directly affects the resulting functionality of the ink layer. Design/methodology/approach: In this work, an automatic lab-scale screen printer was used to print functional inks on a paper board substrate. The printing parameters, i.e. printing pressure and squeegee angle were altered and the resulting effects on the quantity of ink that was deposited were recorded. The quantity of ink deposit was related to its surface resistivity. In addition, the quality of the print was also assessed by examining the design registration quality. Findings: The authors found that altering the squeegee angle has a significant effect on the properties of the resulting ink deposit. More importantly, the authors found that the deflection in the rubber blade squeegee was greatly dependent on the initial angle of the squeegee at the start of the printing stroke. For each set value of the squeegee angle that was considered, the actual angle during printing was recorded and used in the analysis. A printing pressure of three bars and squeegee angle of 20° resulted in the maximum weight of ink deposit with a correspondingly lowest surface resistivity. Practical implications: This study is envisaged to have considerable practical implications in the rapidly growing field of functional printing of flexible substrates including, but not limited to, textiles. This is because, the study provides an insight into the effects of printing parameters on the characteristics of a functional ink deposit. Originality/value: Screen printing of flexible substrates is a well-developed and arguably the most widely used printing technique, particularly for textiles. Numerous studies report on the analysis of various aspects of screen printing. However, to the best of the knowledge, the effects of printing parameters on the characteristics of functional inks, such as electrically conductive inks, have not been studied in this manner.